Development of a golf-specific load monitoring tool: Content validity and feasibility - Williams, S. B.; Gastin, P. B.; Saw, A. E.; Robertson, S. (European Journal of Sport Science, 2018)
Athletes often record details of their training and competitions, supported by information such as environmental conditions, travel, as well as how they felt. However, it is not known how prevalent these practices are in golfers, or how valuable this process is perceived. The purpose of this study was to develop a golf-specific load monitoring tool (GLMT), and establish the content validity and feasibility of this tool amongst high-level golfers. In the first phase of development, 21 experts were surveyed to determine the suitability of items for inclusion in the GLMT. Of the 36 items, 21 received >78% agreement, a requirement to establish content validity and for inclusion in the GLMT. Total duration was the preferred metric for golf-specific activities, whilst rating of perceived exertion (RPE) was preferred for measuring physical training. In the second phase, feasibility of the tool was assessed by surveying 13 high-level male golfers following 28-days of daily GLMT use. All items included in the GLMT were deemed feasible to record, with all players participating in the feasibility study providing high to very high ratings. Golfers responded that they would consider using a load monitoring tool of this nature long term, provided it can be completed in less than five minutes per day.